2017
DOI: 10.1590/abd1806-4841.20175701
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of elderly patients with non-melanoma skin cancer seen at the dermatology outpatient clinic of a public hospital

Abstract: Basal cell carcinoma and Squamous cell carcinoma, referred to as non-melanoma skin cancer, are the most common malignancies in humans. Their incidence is increasing worldwide every year. In Brazil, even with the advent of educational campaigns on photoprotection and laws that banned tanning beds, they are the most frequent neoplasias, representing a public health problem recognized by the Ministry of health. Keywords: Aged care; Carcinoma, basal cell; Carcinoma, squamous cell; Social conditions; Elderly; Neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Actinic and skin cancers are generally found in middle-aged and elderly fair-skinned individuals living in sunny areas, such as Australia and South Africa 94 . An estimated 80% of skin cancers are diagnosed in those aged over 55 years 95 . A recent study performed at the Skin Oncology Sector of the Dermatology Outpatient Clinic of the Santa Casa de Misericórdia de São Paulo (not yet published), revealed that the age of 945 patients with first-time non-melanoma skin cancer (NMSC) averaged 68 years, while 1.7% were under 40 years of age and 90.3% were over 50 years.…”
Section: Climatic Factors and Skin Cancer In Albinismmentioning
confidence: 99%
“…Actinic and skin cancers are generally found in middle-aged and elderly fair-skinned individuals living in sunny areas, such as Australia and South Africa 94 . An estimated 80% of skin cancers are diagnosed in those aged over 55 years 95 . A recent study performed at the Skin Oncology Sector of the Dermatology Outpatient Clinic of the Santa Casa de Misericórdia de São Paulo (not yet published), revealed that the age of 945 patients with first-time non-melanoma skin cancer (NMSC) averaged 68 years, while 1.7% were under 40 years of age and 90.3% were over 50 years.…”
Section: Climatic Factors and Skin Cancer In Albinismmentioning
confidence: 99%
“…Frequencies ( n ) and percentages summarized dichotomous variables and categorical observations. Differences were compared with Student's t -test, Fisher's exact test, or Pearson's χ 2 test. Use of nonparametric Mann–Whitney test or Wilcoxon rank-sum methods depended on the distribution of data.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological estimates indicate a disproportionate surge of nonmelanoma skin cancer (NMSC) in the elderly, with 80% of all new cases occurring in persons >65 years. 1 , 2 As a result of longer life expectancy and the cumulative impact of ultraviolet radiation and sun exposure on anatomically vulnerable sites such as the face, head, and neck, older individuals may develop multiple tumors in localized regions. 3 , 4 This necessitates repeat surgical management that maintains a delicate balance between adequate excision, aesthetics, and function.…”
Section: Introductionmentioning
confidence: 99%